Power quality analysis and mitigation - Charles, Udechukwu Chukwuemeka (2011)
Due to increasing complexity in the power system, voltage sags and swells are now becoming one of the most significant power quality problems. Voltage sag is a short reduction voltage from nominal voltage, occurs in a short time, voltage swell is an increase in the r.m.s voltage from its nominal voltage; they are bound to have a greater impact on the industrial customers. If the voltage sags exceed two to three cycles, then manufacturing systems making use of sensitive electronic equipments are likely to be affected leading to major problems. It ultimately leads to wastage of resources (both material and human) as well as financial losses. The increasing competition in the market and the declining profits has made it pertinent for the industries to realize the significance of high-power quality. This is possible only by ensuring that uninterrupted flow of power is maintained at proper voltage levels. Electric utilities are looking for solutions to ensure high quality power supply to their customers, a lot of solutions have been developed, but this project tends look at the solving the problems by using custom power devices such as Dynamic Voltage Restorer (DVR) and Distribution Static compensator (D-STATCOM). The Dynamic Voltage Restorer appears to be an especially good solution in the current scenario. This work describes the techniques of correcting the supply voltage sag and voltage swell in a distributed system. At present, a wide range of very flexible controllers, which capitalize on newly available power electronics components, are emerging for custom power applications. Among these, the distribution static compensator and the dynamic voltage restorer are most effective devices, both of them based on the VSC principle. A DVR injects a voltage in series with the system voltage and a DSTATCOM injects a current into the system to correct the voltage sag, swell and interruption. Comprehensive results are presented to assess the performance of each device as a potential custom power solution